Climate adaptive solution for artificial turf in cities: integrated rainwater storage and evaporative cooling - van Huijgevoort, Marjolein H. J.; Cirkel, Dirk Gijsbert; Voeten, Joris G. W. F. (Frontiers in Sustainable Cities, 2024)
The number of artificial turf fields in cities has increased due to increased pressure on outside sport facilities caused by a higher population density. Downsides of these fields are changes in thermal conditions and decreased infiltration of rain. Artificial turf can reach very high surface temperatures leading to unfavourable playing conditions and contributing to the urban heat island effect. In this study the possibilities of a subsurface water storage and capillary irrigation system for evaporative cooling of artificial turf based on rainwater capture, storage and reuse are investigated. The system consists of an 85 mm water-retention subbase with capillary columns, a capillary shockpad and a natural infill. First, a laboratory experiment was conducted to test the evaporative potential of the system with different types of infill and artificial turf. Next, four research plots were designed in Amsterdam, The Netherlands, which consisted of natural grass, conventional artificial turf and two versions of the cooled artificial turf system (non-infill and standard). Evaporation from the cooled artificial turf reached maximum values around 4 mm/d during summer and surface temperatures were significantly lower than at the conventional artificial turf. Rainwater was stored below the fields. By combining these functions, these fields can help cities adapt to climate change.